Exploring the challenges in adopting Occupational Safety and Health (OSH) Management Standards and Critical Success Factors for OSH Management System Implementation in Public Universities: A Qualitative Study - Zainal Abidin, Emilia; Ismail, Noor Hassim; Ramat, Hamdan; Zulkifli, Aziemah; Ahmad Mahmmud, Nur Muslihah (WHO Office in Azerbaijan, 2024)
This study explores the challenges in adopting Occupational Safety and Health Management Systems (OSHMS) and Critical Success Factors (CSFs) for Management Standards (MS) implementation in public universities in Malaysia. Using a qualitative, grounded theory approach, six public universities were studied—three with OSHMS certification and three without. Purposive sampling and in-depth interviews with nine key informants were conducted. Thematic analysis approach guided by socio-technical theory were used for synthesising the results. This study protocol has obtained approved from an Institutional Review Board. This study identified barriers such as limited budgets, lack of competence, management awareness, employee participation and the absence of performance metrics. Key CSFs includes internal and external factors namely top management commitment, leadership, competence, resources and directives from authorities. The study concludes that both internal and external authority play critical roles in driving MS adoption. University management must address challenges and leverage existing CSFs within the OSHMS framework to ensure the health and well-being of all interested parties. External policy shifts towards integrating OSH into benchmarking metrics could further support these efforts, aligning with national sustainable development goals.